PENGARUH MODEL PEMBELAJARAN TANDUR TERHADAP PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP DAN PENALARAN MATEMATIS PESERTA DIDIK - Titin Puji Astuti; Rubhan Masykur; Dona Dinda Pratiwi (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The aims of this research to gain the result of effect TANDUR model to mathematical concept understanding and student’s mathematical reasoning. This research was quasi experiment with pretest-postest control group design. The population in this research was students of seventh grade SMP N 2 Natar academic year 2017/2018. The sampling technique used random sampling technique and divided onto two groups, experiment group and control group. The results of this research were: 1) there was influence of TANDUR learning model to mathematical concept understanding. 2) there were influence of TANDUR learning model to mathematical reasoning. 3) TANDUR model learning can affect simultaneously of mathematical concept understanding and mathematical reasoning.